Decreased Bacterial Diversity Characterizes the Altered Gut Microbiota in Patients With Psoriatic Arthritis, Resembling Dysbiosis in Inflammatory Bowel Disease. Issue 1 (January 2015) - Scher, Jose U.; Ubeda, Carles; Artacho, Alejandro; Attur, Mukundan; Isaac, Sandrine; Reddy, Soumya M.; Marmon, Shoshana; Neimann, Andrea; Brusca, Samuel; Patel, Tejas; Manasson, Julia; Pamer, Eric G.; et al.
<x xml:space="preserve">Abstract</x> Objective To characterize the diversity and taxonomic relative abundance of the gut microbiota in patients with never‐treated, recent‐onset psoriatic arthritis (PsA). Methods High‐throughput 16S ribosomal RNA pyrosequencing was utilized to compare the community composition of gut microbiota in patients with PsA (n = 16), patients with psoriasis of the skin (n = 15), and healthy, matched control subjects (n = 17). Samples were further assessed for the presence and levels of fecal and serum secretory IgA (sIgA), proinflammatory proteins, and fatty acids. Results The gut microbiota observed in patients with PsA and patients with skin psoriasis was less diverse when compared to that in healthy controls. This could be attributed to the reduced presence of several taxa. Samples from both patient groups showed a relative decrease in abundance of Coprococcus species, while samples from PsA patients were also characterized by a significant reduction in Akkermansia, Ruminococcus, and Pseudobutyrivibrio. Supernatants of fecal samples from PsA patients revealed an increase in sIgA levels and decrease in RANKL levels. Analysis of fatty acids revealed low fecal quantities of hexanoate and heptanoate in both patients with PsA and patients with psoriasis. Conclusion Patients with PsA and patients with skin psoriasis had a lower relative abundance of multiple intestinal bacteria. Although some genera were concomitantly decreased in both conditions, PsA samples had a lower abundance of reportedly beneficial taxa. This gut microbiota profile in PsA was similar to that previously described in patients with inflammatory bowel disease and was associated with changes in specific inflammatory proteins unique to this group, and distinct from that in patients with skin psoriasis and healthy controls. Thus, the role of the gut microbiome in the continuum of psoriasis–PsA pathogenesis and the associated immune response merits further study.